2017
DOI: 10.1111/jocn.13485
|View full text |Cite
|
Sign up to set email alerts
|

The impact of single and shared rooms on family‐centred care in children's hospitals

Abstract: Aim: T rooms) impact upon family centred care.Background: Family centred care has been widely adopted in paediatric hospitals internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
2
41
0
2
Order By: Relevance
“…Often, the arrangement of furniture in the wards does not ease the work of the professionals but, rather, hampers the actions of comprehensive care, especially regarding the needs of the families and children/adolescents. A study (18) from England emphasizes the need to respect confidentiality and privacy of the children/adolescents and their families, since the relationships and interactions among children, parents and the team can be significantly affected by the type of organization of the hospital spaces.…”
Section: This Communication Must Improve and The Professional Must Nomentioning
confidence: 99%
“…Often, the arrangement of furniture in the wards does not ease the work of the professionals but, rather, hampers the actions of comprehensive care, especially regarding the needs of the families and children/adolescents. A study (18) from England emphasizes the need to respect confidentiality and privacy of the children/adolescents and their families, since the relationships and interactions among children, parents and the team can be significantly affected by the type of organization of the hospital spaces.…”
Section: This Communication Must Improve and The Professional Must Nomentioning
confidence: 99%
“…Many studies have shown that single family rooms promote family privacy and FCC in critical care settings (adult intensive care unit and neonatal intensive care unit [NICU]) . Others have indicated the potential risks of isolating families away from nurses (paediatric hospital and NICU) . In a study of seven open‐bay NICUs, Al‐Motlaq found that unit design hindered the provision of FCC.…”
Section: Introductionmentioning
confidence: 99%
“…This family presence is a support for their child and participation in the care, planning and decision‐making empowers parents and make them feel part of their child's care (Wieczorek, Nowak, Frampton, & Pelikan, ). Indeed there is now a tripartite expectation, from child, nurse, and family that basic care needs are provided by the family (Curtis & Northcott, ). In fact, families will arrange ‘cover’ for one another when taking breaks, rather expecting the child's surveillance and care to be done by nursing staff (Curtis & Northcott, ).…”
mentioning
confidence: 99%